Analisis Peran Koperasi dalam Pengelolaan Hutan Rakyat di Kebumen - Elok Budiningsih; Harjanto Harjanto; Yulius Hero (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Community forests are a viable alternative for timber suppliers. Community forestry institutions are required to ensure its sustainability. Cooperatives become one of the appropriate alternatives in accordance with the institution at the site level in community forest development. One of the peasant organizations that manages the human resources in the form of cooperatives is a Taman Wijaya Rasa Cooperative (Kostajasa) located in Kebumen. This study aims to analyze the role of Kostajasa in community forest management. The descriptive analysis used in describing the role of Kostajasa in community forest management supporting three community forest subsystems, namely production, processing and marketing subsystem. Kostajasa has played a good role in all three subsystems. In the production subsystem, there are still less roles in the determination of timber products to be managed, and setting the felling regulation. In the processing subsystem Kostajasa have already play a good role to connect several industries to receive raw materials from farmers’ timber and maintain the demand continuity for raw materials so that farmers’ timber is absorbed. In the marketing subsystem, Kostajasa also play a good role among others, shorten the marketing chain of wood products from community forest and offering a better price outside Kostajasa.